The Effects of Concurrent Training Combining Both Resistance Exercise and High-Intensity Interval Training or Moderate-Intensity Continuous Training on Metabolic Syndrome - Da Silva, Marco Antônio R.; Baptista, Liliana C.; Neves, Rafael S.; De França, Elias; Loureiro, Helena; Lira, Fabio Santos; Caperuto, Erico C.; Veríssimo, Manuel T.; Martins, Raul A. (Frontiers in Physiology, 2020)
To date, there are several knowledge gaps on how to properly prescribe concurrent training to achieve the best dose-response, especially regarding the optimal intensity or volume of the aerobic component. Thus, the objective of this study is to analyze the effects of different aerobic exercise modes and intensities (i.e. aerobic high-intensity interval training (HIIT) versus moderate-intensity continuous aerobic training (MICT) combined with a resistance training (RT) program) on metabolic outcomes in participants with metabolic syndrome (MetS). Thirty-nine men and women (67.0 ± 6.7 years) volunteered to a 12-weeks exercise intervention (3·week-1, 50 minutes/session) and were randomly assigned to one of three groups: a) RT plus MICT (RT+MICT) (2 males; 11 females); b) RT plus HIIT (RT+HIIT) (4 males; 9 females); and c) control group (CON) - without formal exercise (4 males; 9 females). Intensity was established between 60-70% of maximum heart rate (HRmax) in RT+MICT and ranged from 55-65% to 80-90% HRmax in the RT+HIIT group. Dependent outcomes included morphological, metabolic and hemodynamic variables. Both training groups improved waist circumference (RT+MICT: P = 0.019; RT+HIIT: P = 0.003), but not body weight, fat mass or fat-free mass (P ≥ 0.114). RT+HIIT group improved fasting glucose (P = 0.014), low density lipoprotein (P = 0.022), insulin (P = 0.034) and homeostatic model assessment (P = 0.028). RT+MICT group reduced triglycerides (P = 0.053). Both exercise interventions did not change high sensitivity C-reactive protein, glycated hemoglobin, high density lipoprotein and total cholesterol, systolic, diastolic or mean arterial blood pressure (P ≥ 0.05). The CON group did not change any outcome measure. This trial suggests that short-term exercise mode and intensity may differently impact the metabolic profile of individuals with MetS. Further, our data suggests that both concurrent trainings promote important cardiometabolic gains, particularly in the RT+HIIT. Nonetheless, due to the small-to-moderate effect size and the short-term intervention length, our data suggests that the intervention length also has an important modulating role in these benefits in older adults with MetS. Therefore, more research is needed to confirm our results using longer exercise interventions and larger groups.